“Were There Any Black People in Johnstown?” An Investigation of Culturally Relevant Pedagogy in Service of Supporting Disciplinary Literacy Learning in History - Kucan, Linda; Cho, Byeong-Young (Urban education (Beverly Hills, Calif.), 2022)
This case study describes how culturally relevant pedagogy can be used in disciplinary rigorous ways in an urban middle school history classroom. The focus is on a unit about the Johnstown Flood of 1889, which provided a setting for teaching about the event as well as the historical thinking practices of contextualizing, sourcing, and corroborating. The teacher supported students’ cultural and academic competence for learning both historical content and historical thinking about that content by capitalizing on their funds of knowledge, making use of accessible cultural referents, and sharing personal narratives.